Comparative analyses of chloroplast genomes of Theobroma cacao from northern Peru - Daniel Tineo; Danilo E. Bustamante; Martha S. Calderon; Manuel Oliva (PLoS ONE, 2025)
Theobroma cacao is the most economically important species within the genus Theobroma. Despite its importance, the intraspecific relationships of this species has not been fully elucidated due to insufficient molecular information. To facilitate a better understanding of the intraspecific evolutionary relationships of T. cacao, Sequencing technology has been to decode the plastid genomes, with the objective of identify potential DNA barcode genetic markers, explore intraspecific relationships, and infer divergence times. The plastid genome of the seven cocoa genotypes analyzed in this study, exhibited a typical angiosperm genomic structure. However, the structure of each plastid genome reflects notable changes in each genotype; for example, the infA gene was present in all the analyzed samples, unlike in previously published cocoa plastid genomes, while the complete ycf1 gene sequence has potential for use as DNA Barcoding in T. cacao. The estimated age of the node connecting T. cacao and T. grandiflorum, which was 10.11 Ma, supports this indication. It can be inferred that T. cacao diverged at approximately 7.55 Ma, and it is highly likely that T. cacao populations diversified during the Pliocene or Miocene. Therefore, it is crucial to perform mitochondrial and nuclear-based analyses on a broader spectrum of cocoa samples to validate these evolutionary mechanisms, including genetic estimates and divergence. This approach enables a deeper understanding of the evolutionary relationships among cocoa.